THE MEANING OF THE CIRCULAR FORMATION OF MOLULO DANCE IN THE CONTEXT OF LOCAL CULTURAL VALUES OF THE TOLAKI TRIBE - Nurachmy Sahnir (Universitas Negeri Makassar, 2022)
Knowledge of the meaning contained in the Molulo dance performance relating to the context of the local cultural values of the Tolaki Tribe in Konawe Regency is contained in the floor pattern in this case a circular formation that contains a meaning based on